'We are trying to live in a normal way, but nothing is normal about us anymore…': a qualitative study of women's lived experiences of healthcare in opposition-controlled areas of Syria. Issue 7 (19th July 2022) - Alhaffar, Mervat; Hamid, Aseel; Douedari, Yazan; Howard, Natasha
Abstract : Introduction: The Syrian conflict, which has included mass killings, displacement, infrastructure destruction and illegal targeting of health facilities and staff mainly by the Syrian government and allies, is in its 10th year. This study explored the lived experiences of women within healthcare, both as health workers and service users, in Syrian opposition-controlled areas (OCAs). Methods: We chose a qualitative study design, with 20 in-depth interviews conducted remotely over WhatsApp and Messenger with purposively sampled Syrian women (ie, 15 health workers, 5 service users). We analysed data using interpretative phenomenological analysis. Results: Anxiety, fear and horror affected women's everyday work and wellness. Excess workload and insecurity were major challenges for women health workers, who also had household and caring responsibilities. Coping mechanisms included: (1) normalising death; (2) acceptance of God's will; and (3) focusing on controllable issues such as health services provision while accepting the reality of insecurity and death. Conflict contributed to changing social norms and expectations, and women became key actors in healthcare provision, though this did not translate directly into greater decision-making authority. Structural biases (eg, lack of maternity leave) and gender-based violence (eg, increased harassment and child marriage) inordinately affected women. Conclusion: This is a first effort to amplify women's voices in health policy and systems research on the Syrian conflict. Women have become key healthcare providers in OCAs but remain under-represented in decision making. While the conflict-related social transformation, increasing the role of—and demand for—women health workers could be viewed positively for women's empowerment, the reality is complex and long-term implications are unclear.